A Hydrolyzable Supra‐amphiphile as a Marangoni Self‐Propulsion Fuel for Efficient Macroscopic Supramolecular Self‐Assembly. (28th February 2023) - Lu, Guoxin; Zhu, Guiqiang; Zhang, Qian; Tian, Pan; Cheng, Mengjiao; Shi, Feng
Abstract: Self‐assembly of μm‐to‐mm components is important for achieving all‐scale ordering with requirements of extra energy for motion and interaction of components. Marangoni flows caused by surfactants on water provide appropriate energy but have limited lifetimes because of the inevitable interfacial aggregation and difficult decomposition of aggregated covalent surfactants that inactivate Marangoni effects. Here we have synthesized a supra‐amphiphile Marangoni "fuel"—sodium‐4‐(benzylideneamino) benzenesulfonate (SBBS)—that can be hydrolyzed in a timely manner to a species without surface activity to extend the motion time by 10‐fold. The motion was optimized at pH=2 by a fine equilibrium between the releasing and removal of interfacial SBBS, leading to the self‐assembly of millimeter‐scaled ordered dimers. The underlying mechanism was interpreted by motion analyses and simulation. This strategy provides an active solution to self‐assembly at the μm‐to‐mm scale, as well as interactive ideas between miniaturized chemical robots. Abstract : A reversible Schiff base has been used as the basis for a fuel for continuous Marangoni self‐propulsion. Excessive interfacial aggregation of the amphiphilic molecules is avoided by timely hydrolyzation to surface‐inactive species, which prolongs the motion lifetime by over 10 times. The fuel can efficiently propel μm‐to‐mm components for the energy‐dissipative self‐assembly of precisely aligned structures.